Enhancing Operational Excellence: Through use TQM, Lean and 6 Sigma - Patil, Avesh; Shamsher, Salim; Basu, Analjyoti (Greenation International Journal of Engineering Science, 2025)
Considering the cutthroat competition organizations are using multiple avenues including operational excellence (OpEx or OE) to enhance processes, improve operational efficiency, and mint products and services with highest quality levels to customers. This study is about use of Quality Tools to achieve the same. This study is also about way these quality tools are used to effectively deliver change of quality levels in the companies. This research also shows that beyond the quality tools there are systematic approaches to improve quality by adopting cluster tools like Total Quality Management (TQM), Six Sigma, Lean Six Sigma, Total Productive Maintenance (TPM), and to some extent Continuous Improvement (CI).